Combination of systemic terbinafine (250 mg) twice daily and itraconazole (100 mg) twice in a pulse dose in resistant tinea infection - Shumi, Farhana R.; Shamim, Sarker M. A.; Afroz, Rabeya; Sharmin, Shumana; Kabir, Sharmin; Mumtaz, Fahima (International Journal of Research in Dermatology, 2022)
Background: The management of tinea is challenging in Bangladesh and there are reports of using systemic antifungals at higher doses. The aim of the study was to find out the effectiveness of systemic terbinafine (250 mg) twice daily and itraconazole (100 mg) twice in a pulse dose in resistant tinea infection. Methods: It was a prospective, observational study conducted in the department of dermatology and venereology, Dhaka Dermatology Institute, Dhaka, Bangladesh from November 2020 to October 2021. Clinically confirmed cases of tinea corporis et cruris were recruited by random sampling techniques for the study and followed up for 12 weeks, till the completion of their treatment. Patients who were pregnant, lactating, non-consensual, as well as those who had a history of anti-mycotic treatment within 2 weeks prior to baseline visit were excluded from the study. Results: A total of 30 patients were randomly assigned treatment and included in the study. According to within 4 weeks 11 (36.33%) patients were significantly improved and 19 (63.33%) patients were non-significantly improved, >4 week to till 8 weeks 16 (84.21%) patients were improved significantly and 3 (15.79%) patients were improved non-significantly and >8 week to till 12 weeks 3 (100%) patients were improved properly. Mycological cure was achieved in 25 (82.89%) patients, clinical cure rate was achieved same in 24 (79%) patients and complete cure rate was achieved 30 (100%) patients. Conclusions: The combination of systemic terbinafine (250 mg) twice daily and itraconazole (100 mg) twice in a pulse dose therapy may be an effective and safe therapeutic strategy in the management of registrant tinea infection.